J Point and ST Elevation Resembling Brugada: A Marker of Mortality in Methanol Toxicity - Mohammad Hossein Nikoo; Alireza Estedal; Kiana Khatami; Maryam Pakfetrat; Alireza Arjangzadeh; Shahrokh Sadeghi Boogar; Sina Danesh; Seyed Taghi Heydari (Cardiology Research and Practice)
Objective. J point and coved ST elevation in right precordial leads (not produced by coronary artery disease) are still a matter of challenge, especially when resembling Brugada patients. This clinical entity, among asymptomatic individuals with no family history of sudden cardiac death, would be reported in some severely ill patients before ventricular fibrillation. This study investigated the relationship between the electrocardiograms with demographic and laboratory data and also analyzed their association with mortality rate among patients with methanol poisoning. Methods. The sample consisted of 356 patients who were hospitalized with a diagnosis of methanol poisoning in Faghihi and Namazi Hospitals in Shiraz, Southern Iran, in March and April 2020. In this period, a major outbreak of methanol poisoning had occurred in this area. Furthermore, the study used the data on any recorded complications or mortality during hospital course. Results. The ECG (BrP) was observed in a total of 20 (5.6%) patients. Its presence was associated with increased mortality, Glasgow coma scale score <3, and blood sugar levels and was inversely associated with PH, O2 saturation, and calcium levels (P<0.05). Conclusions. This study found that certain ECG patterns and laboratory data can be used as prognostic factors of morbidity and mortality in patients with methanol intoxication. Electrocardiography machines are widely available tools, which can be easily used for risk stratification based on the presence of Brugada approximating electrocardiograms among patients with methanol intoxication.